Aplicação da espectrometria de massas ambiente por Paper Spray Ionization na identificação e quantificação de cocaína e no controle de qualidade de bebidas - Tosato, Flávia (2016)
Rapid, inexpensive and efficient analyzes are required for laboratory routines, especially when applied in forensic chemistry. Uses of the environment sources allow the analyzes to be direct and fast. Thus, they are innovative options to improve sensitivity and selectivity. In this work, a methodology was developed using environmental mass spectrometry by paper spray ionization mass spectrometry (PS-MS) for different data matrices: (i) to identify and quantify cocaine and its adulterants from PS-coupled chromatography -MS; (Ii) discriminate or classify ten Brazilian beer brands in pilsen and lager; And (iii) to identify the controlled counterfeit of whiskey with cachaça in order to quantify the volume of cachaça added in the mixture. In the analysis of cocaine and adulterants, the standards were identified in the CCD and analyzed by PS-MS, and a calibration curve was optimized. The beer was previously fractionated using the solid phase extraction (SPE) methodology with water / methanol and the four extracts were characterized in positive ionization mode, PS (+) MS. For both cases, 20 µL of the analyte was applied to the PS-MS paper surface. In the quantification of cachaça in blends of whisk-cachaça. The results indicate that the use of Cdc coupled to PS-MS allows the identification of cocaine and its adulterants. A good linearity for the curves was found (cocaine (R2 = 0.9989), benzocaine, (R2 = 0.9934) Caffeine (R2 = 0.9988), phenacetin (R2 = 0.9966), and lidocaine (R2 = 0.9987)) and LOD lower than that of the CCD technique. For the beer samples the signs of sugars stand out over the other groups, and after extraction with water / methanol it was possible to distinguish the spectra of the different beer brands and classify them in pilsen and lager bythe PCA technique. Using PS (±) -MS and PLS with variable selection it was possible to estimate quantitatively the cachaça content mixed with whiskey. With this, the use of environmental sources, such as PS, is effective for identification of several matrices, facilitating routine analyzes